Influential and Intellectual Structure of Geopolymer Concrete: A Bibliometric Review - Salam Al-Kasassbeh; Jafar Al-Thawabteh; Eslam Al-Kharabsheh; Amani Al-Tamseh (Salehan Institute of Higher Education, 2023)
The objective of this bibliometric review is to deliver an in-depth examination of the dynamic field of geopolymer concrete, revealing its evolution, current trends, and possible future trajectories. The method involves a rigorous bibliometric analysis of research output since the field's inception in 2003, underlining key milestones and mapping research patterns. Findings show a consistent surge in geopolymer concrete research, exemplified by over 1360 annual publications, with notable contributions predominantly from Australia and India. The paper also uncovers the increasing practical applications of geopolymer concrete, especially in construction processes, underpinned by a wealth of research on fly ash, a crucial manufacturing component. Additionally, prevalent research themes include compressive strength, fly ash, and geopolymer itself. The review's novelty lies in its comprehensive overview of geopolymer concrete research, elucidating past and present trends and identifying potential future research areas. It thereby serves as a firm foundation for further studies, fostering continued growth in this promising field.Â Doi: 10.28991/CEJ-2023-09-09-017 Full Text: PDF